Hadits tentang Dzikir Perspektif Tasawuf - Resti Widianengsih (Jurnal Penelitian Ilmu Ushuluddin, 2022)
The background of this research is that dhikr in the hadith of the Prophet SAW has an attachment to other teachings, such as dhikr and Sufism. Dhikr and Sufism are seen as a medium of communicating with Allah SWT to know and be closer to Him and make the heart and soul calm and noble. This study aims to discuss the hadith about dhikr in the perspective of Sufism. This research is a qualitative type through literature study with the method of syarah hadith and analysis of Sufism. The results and discussion show that dhikr can revive the heart from death, namely a heart that does not remember the greatness of Allah SWT, this is in accordance with the hadith of the Prophet SAW from Abu Musa Asy'ari that the parable of a person who makes dhikr and someone who does not remember Allah is like a person who remembers Allah live with the dead. This study concludes that the hadith about dhikr according to the review of the hadith syarah with the analysis of Sufism is recommended for dhikr to Allah SWT continuously (mudawammah), because with dhikr, can revive the heart from death. A heart that does not remember the greatness of Allah SWT considered dead by the Sufis. This study recommends to Islamic religious authorities, in order to provide an understanding to the Muslim audience regarding the syarah hadith about dhikr from the Sufism perspective.